2019
DOI: 10.1183/13993003.01504-2019
|View full text |Cite
|
Sign up to set email alerts
|

The ever-expanding phenotypical spectrum of human TBX4 mutations: from toe to lung

Abstract: Since the discovery of the TBX4 gene, the phenotypical spectrum of human TBX4 mutations is rapidly expanding from syndromes with skeletal dysplasia, to pulmonary hypertension to developmental lung diseases, all associated with disrupted organ development http://bit.ly/2MvYful

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…In the light of the growing insight in the heterogeneous phenotypes of human TBX4 variants, the authors recommend a meticulous and focused diagnostic work-up in patients with PH and a TBX4 variant in order to be able to start the most appropriate treatment. 28,29 In the current study, one patient with a TBX4 variant had a histopathologic diagnosis of PVOD, confirmed at autopsy. As far as we know, the concomitant occurrence of a TBX4 mutation and PVOD has not been described before.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the light of the growing insight in the heterogeneous phenotypes of human TBX4 variants, the authors recommend a meticulous and focused diagnostic work-up in patients with PH and a TBX4 variant in order to be able to start the most appropriate treatment. 28,29 In the current study, one patient with a TBX4 variant had a histopathologic diagnosis of PVOD, confirmed at autopsy. As far as we know, the concomitant occurrence of a TBX4 mutation and PVOD has not been described before.…”
Section: Discussionsupporting
confidence: 53%
“…9,10 The clinical phenotype associated with TBX4 variants has been recently recognized to expand beyond HPAH, including a spectrum of ''developmental'' or interstitial lung disorders and respiratory compromise that may present in newborns, associated with persistent pulmonary hypertension of the newborn, but also during adulthood. [23][24][25][26][27][28][29] This expanding spectrum will complicate classification of such patients according to the clinical classification of pulmonary hypertension as either HPAH or PH due to lung disease. In the light of the growing insight in the heterogeneous phenotypes of human TBX4 variants, the authors recommend a meticulous and focused diagnostic work-up in patients with PH and a TBX4 variant in order to be able to start the most appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The most severely affected skeletal elements are also the same as those affected in human ischiocoxopodopatellar syndrome (OMIM: 147891), an autosomal dominant disorder caused by mutation in the TBX4 gene. The main clinical features of this syndrome include anomalies of the pelvis and femur, aplastic or hypoplastic patella and anomalies of the feet that are believed to originate from TBX4 haploinsufficiency ( Bongers et al, 2004 ; Haarman et al, 2019 ). In addition, TBX4 homozygous null mutations have been reported to lead to posterior amelia with pelvic hypoplasia ( Kariminejad et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phocomelia is a congenital limb malformation in which the proximal portion of the limb (Bongers et al 2004, Haarman et al 2019). In addition, TBX4 homozygous null mutations have been reported to lead to posterior amelia with pelvic hypoplasia (Kariminejad et al 2019).…”
Section: Development • Accepted Manuscriptmentioning
confidence: 99%
“…Mutations in the transcription factor TBX4 have recently been found to cause acinar dysplasia, a disorder involving profound disruption of lung development at the canalicular phase. However, TBX4 mutations also cause skeletal abnormalities that are not uniformly present in all subjects, and TBX4 mutations are also being increasingly recognized as a cause of pulmonary hypertension in children 11 . The reasons for this phenotypic variability remain unknown but may be explained in part that infants with acinar dysplasia and TBX4 mutations have also been found to have mutations in other genes that may impact the phenotype.…”
Section: Introductionmentioning
confidence: 99%